1982
DOI: 10.1002/ana.410120406
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and clinical correlation in myasthenia gravis

Abstract: Repetitive nerve stimulation testing of the ulnar nerve was systematically performed on 21 normal controls and 120 patients with myasthenia gravis (MG). Diagnostic sensitivity increased from 0% in MG in remission and 17.2% in ocular MG to 100% in severe generalized MG. Six types of responses were observed in MG and could be classified into two distinct patterns based upon disease severity: ( 1 ) in mild MG, an abnormal decremental response at low rate of stimulation, normal response at high rate of stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0
3

Year Published

1983
1983
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 20 publications
1
66
0
3
Order By: Relevance
“…EMG repetitive stimulation was useful in the diagnosis of our patients but, like others we found that its sensitivity correlated with the form and severity of the disease it is low in the ocular forms, increases in the generalized forms and is even higher the more severe the disease is manifested [17][18][19] .…”
Section: Discussionmentioning
confidence: 86%
“…EMG repetitive stimulation was useful in the diagnosis of our patients but, like others we found that its sensitivity correlated with the form and severity of the disease it is low in the ocular forms, increases in the generalized forms and is even higher the more severe the disease is manifested [17][18][19] .…”
Section: Discussionmentioning
confidence: 86%
“…15,20 In general, about 60-85% of patients with myasthenia gravis show a decremental response. 5,15,16 Diagnostic sensitivity increases with increasing severity of myasthenia gravis, 15,16 with positive results in 14-38% of patients with ocular involvement only (Osserman class 1) and in 83-100% of patients with an incapacitating weakness of any muscle system (Osserman class IV).…”
Section: Discussionmentioning
confidence: 99%
“…15,20 In general, about 60-85% of patients with myasthenia gravis show a decremental response. 5,15,16 Diagnostic sensitivity increases with increasing severity of myasthenia gravis, 15,16 with positive results in 14-38% of patients with ocular involvement only (Osserman class 1) and in 83-100% of patients with an incapacitating weakness of any muscle system (Osserman class IV). 3,15,16 Only 1 of our 4 patients had decremental responses on initial assessment during the period of respiratory failure, despite all being Osserman class IV and all having careful repetitive stimulation studies of the median and facial nerves.…”
Section: Discussionmentioning
confidence: 99%
“…351 amplitude in response to repetitive nerve stimulation, single fiber electromyography, stapedius reflex fatiguability, tests for eye movement fatigue and detection of antibodies against the acetylcholine receptors in the serum. Many of these tests have limitations in diagnosing ocular myasthenia gravis (Oh et al 1982;Kelly et al 1982).…”
mentioning
confidence: 99%